(untitled) (Bioresearch Communications, 2024)
Thirty species of Ascomycetous fungi under 21 genera belonging to 12 Families in Bangladesh from 1952 till date are enlisted. The alphabetical checklist of the genera is provided herewith. Further updates will be added in the subsequent versions of the publication. Bioresearch Commu. 11(1): 1627-1632, 2025 (January)